Social Media Marketing, e-WOM, and Purchase Decisions: The Mediating Role of Brand Trust - Tifani Rahma Aulia; Anik Lestari Andjarwati (Harmoni Economics: International Journal of Economics and Accounting, 2026)
The rapid growth of digital technology and e-commerce has transformed consumer behavior, particularly in the skincare industry. This study investigates the influence of Social Media Marketing (SMM) and electronic Word-of-Mouth (e-WOM) on online purchase decisions, with Brand Trust as a mediating variable. Data were collected from 205 Shopee consumers of the skincare brand Skin1004 using an online questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed using SmartPLS 4 to assess the measurement model, structural model, and mediation effects. The results reveal that both SMM and e-WOM significantly enhance Brand Trust and Purchase Decisions. Additionally, Brand Trust partially mediates the relationships between SMM and Purchase Decisions and between e-WOM and Purchase Decisions. These findings underscore the pivotal role of Brand Trust in optimizing social media marketing and e-WOM strategies to influence consumer purchasing behavior in e-commerce settings.